2023
DOI: 10.3390/pr11030771
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of a Class I Gas Hydrate Reservoir Depressurized by a Fishbone Well

Abstract: The results of the second trial production of the gas hydrate reservoir in the Shenhu area of the South China Sea show that the production of a gas hydrate reservoir by horizontal wells can greatly increase the daily gas production, but the current trial production is still far below the minimum production required for commercial development. Compared with a single horizontal well, a fishbone well has a larger reservoir contact area and is expected to achieve higher productivity in the depressurization develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The study conducted by He [60] primarily investigated the application of fishbone wells for the extraction of gas hydrates from reservoirs, using the Shenhu area of the South China Sea as a case study. The research indicated that whereas the use of horizontal wells significantly improved daily gas production, it still fell short of the minimum threshold required for commercial exploitation.…”
Section: Gas Hydratementioning
confidence: 99%
“…The study conducted by He [60] primarily investigated the application of fishbone wells for the extraction of gas hydrates from reservoirs, using the Shenhu area of the South China Sea as a case study. The research indicated that whereas the use of horizontal wells significantly improved daily gas production, it still fell short of the minimum threshold required for commercial exploitation.…”
Section: Gas Hydratementioning
confidence: 99%
“…Jin G. et al estimated that 22 sets of multilateral wells each with a completion length of 1000 m are sufficient to achieve commercial development of NGHs in China's Shenhu Sea area [22]. He J. et al simulated the productivity of a fishbone well with different lateral branch numbers and found that the production capacity of the six-branch fishbone well was about 59.3% higher than that of the single horizontal well [23].…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al used a single horizontal well system and a dual horizontal well system to simulate the long-term NGHs production behavior and found that the extremely low permeability makes it difficult to significantly increase gas production. He found through that using multibranch fishbone wells for depressurization can effectively increase the cumulative gas production in the trial production area. Zhu et al demonstrated through numerical simulation that placing a horizontal well in the three-phase layer (TPL) and approaching the bottom of the TPL can achieve higher gas production.…”
Section: Introductionmentioning
confidence: 99%